An Innovative Model for Integrating Human Rights in Islam in the Curriculum of Islamic Education for the Seventh Grade in Palestine in light of contemporary challenges (The International Journal for Scientific Research, 2025)
The aim of this study was to develop an innovative model for integrating human rights in Islam into the Islamic education curriculum for the  Seventh basic grade, with the aim of enhancing students' awareness of their rights based on the content analysis of the Islamic education curriculum for grades 5-9 in Palestine in the light of human rights in Islam.), which starts with identifying the desired educational outcomes, then identifying the appropriate assessment tools, and ending with the design of applied educational activities, linking each goal to a concrete practical merit. This methodology was chosen because of its compatibility with the philosophy of Islamic education, which pairs faith with action, and its suitability for the nature of the proposed matrix that aims to transform human rights in Islam from theoretical concepts to practical values and behaviors practiced by students in their daily lives. The results and recommendations showed the importance of developing this model, given the linkage of Islamic education curricula to the political, civil, social, cultural and economic aspects of human life, to fill the gaps revealed by the study, and to support the developers of Islamic education curricula in Palestine to develop them in accordance with the principles of human rights in Islam and the age stage, by taking advantage of the practical procedures and suggestions contained in the model to address the weaknesses and shortcomings in the curriculum to face the contemporary challenges that showed the inability of the UN institutions to perform their role in accordance with the of the Positive Law on Human Rights of 1948.
Keywords: Islamic Education Curricula; Upper Basic Stage; Palestine; Human Rights in Islam